The long-term (24-month) effect on health and well-being of the Lifestyle Matters community-based intervention in people aged 65 years and over: a qualitative study. Issue 9 (24th September 2017) - Chatters, Robin; Roberts, Jennifer; Mountain, Gail; Cook, Sarah; Windle, Gill; Craig, Claire; Sprange, Kirsty
Abstract : Objectives: To assess the long-term effect on health and well-being of the Lifestyle Matters programme. Design: Qualitative study of a subset of intervention arm participants who participated in the Lifestyle Matters randomised controlled trial (RCT). Setting: The intervention took place at community venues within two sites in the UK. Participants: A purposeful sample of 13 participants aged between 66 and 88 years from the intervention arm of the RCT were interviewed at 24 months post randomisation. Interviews aimed to understand how participants had used their time in the preceding 2 years and whether the intervention had any impact on their lifestyle choices, participation in meaningful activities and well-being. Intervention: Lifestyle Matters is a 4-month occupational therapy intervention, consisting of group and individual sessions, designed to enable community living older people to make positive lifestyle choices and participate in new or neglected activities through increasing self-efficacy. Results: Interviews revealed that the majority of interviewed participants were reportedly active at 24 months, with daily routines and lifestyles not changing significantly over time. All participants raised some form of benefit from attending Lifestyle Matters, including an improved perspective on life, trying new hobbies and meeting new friends. A number of intervention participants spoke of adapting to their changing circumstances, but there were significant and lasting benefits for 2 of 13 intervention participants interviewed. Conclusion: The majority of those who experienced the Lifestyle Matters intervention reported minor benefits and increases in self-efficacy, but they did not perceive that it significantly improved their health and well-being. The two participants who had experienced major benefits also reported having had life-changing events, suggesting that this intervention is most effective at the time when lifestyle has to be reconsidered if mental well-being is to be sustained. Trial registration: ISRCTN, ISRCTN67209155, post results.